The incidence and management of non-head and neck incidentalomas for the head and neck surgeon. (November 2017) - Sahovaler, Axel; Yeh, David H.; Morrison, Deric; de Ribaupierre, Sandrine; Izawa, Jonathan; Power, Adam; Inculet, Richard; Parry, Neil; Palma, David A.; Landis, Mark; Leung, Andrew; Fung, Kevin; et al.
Highlights: 38% of 779 HN cancer patients had at least one non-head and neck incidentaloma. 20% of all non-HN incidentalomas had no recommendations in the radiology report. Most common locations were lung (15%), liver (10.6%) and kidney (5.6%) Some of these incidental findings can have serious consequences if left untreated.